States and statistics in the nineteenth century Europe by numbers - Randeraad, Nico (2010)
This book is a history of an illusion. It is also a history of the dream that preceded the illusion. The book discusses statistics as the field of tension between the scientific claims of neutrality and universality on the one hand and the political and economic reality of the conflicting interests of nation-states on the other. The various paths of state- and nation-building that European countries traversed in the nineteenth century are recognisable in the objectives of government statistics and are reflected in the topics selected for statistical study and in the categories used in the research. Each congress was clearly dominated by the specific interests of the country in which the statisticians convened. The book shows in each case how the organisation of government statistics and national concerns influenced the international agenda. It describes the perceptions, goals and dilemmas of the protagonists and their contact with each other, and in so doing unravels the complex relationships between science, government and society, wherever possible from their point of view. The genesis of international statistics was inspired by a desire for reform. Belgium's pioneering role in the European statistical movement was informed both by its liberal polity and the special status of statistics within it, and by Adolphe Quetelet's key position as an intellectual. The consolidation of the Grand Duchy of Baden, a new medium-sized state in the Rhine Confederation and later in the German Confederation, offered great opportunities for the development of official statistics